(untitled) (Bangladesh Journal of Bioethics, 2020)
In the past few years, Bioethics, the branch of applied ethics, has been widely established as a discipline, as a value framework, a framework of principles, a tool, as a medium for practical skill development to help individuals understand complex moral, social, legal, environmental issues in medicine, clinical and health research. As a discipline, bioethics invite interdisciplinary deliberation and draws people from all sectors of society to engage in discussion. Bioethics also serves as the potential medium for greater community engagement and participation involving both professionals and non-professionals. With the evolution of the branch, Bioethics education has rapidly developed over the last few decades. It has been extended to be a part of academic curriculum with the purpose to help students develop the critical thinking skills in dealing with complicated ethical issues; to develop the skill of rational argumentation, reasoned responses. The papers in this issue on Bioethics and Educational Institutes emphasize the need and practical implications of incorporation of Bioethics in the academic curriculum across the globe.